2014
DOI: 10.1200/jco.2013.54.1870
|View full text |Cite
|
Sign up to set email alerts
|

Luminal B Breast Cancer: Molecular Characterization, Clinical Management, and Future Perspectives

Abstract: Gene expression profiling has reshaped our understanding of breast cancer by defining and characterizing four main intrinsic molecular subtypes: human epidermal growth factor receptor 2-enriched, basal-like, luminal A, and luminal B subtypes. Luminal B breast cancer has been reported to have lower expression of hormone receptors, higher expression of proliferation markers, and higher histologic grade than luminal A. It also exhibits worse prognosis and has a distinct profile of response to hormone therapy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
281
3
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 336 publications
(306 citation statements)
references
References 115 publications
13
281
3
9
Order By: Relevance
“…However, molecular studies have shown that luminal B is not simply a more proliferative variant of luminal A, because both luminal A and B cancers have their own specific oncogenic drivers. 80 The IHC definition for this subgroup is less well defined. Originally, ER þ and PR À , 81 or ER þ and HER2 þ , 82 was used, but later most investigators used ER þ and HER2 À to describe this subtype if the score of Ki-67 was 14% or higher, 25,52 or higher than 20%.…”
Section: Ihc-based MC Er-positive Bcmentioning
confidence: 99%
“…However, molecular studies have shown that luminal B is not simply a more proliferative variant of luminal A, because both luminal A and B cancers have their own specific oncogenic drivers. 80 The IHC definition for this subgroup is less well defined. Originally, ER þ and PR À , 81 or ER þ and HER2 þ , 82 was used, but later most investigators used ER þ and HER2 À to describe this subtype if the score of Ki-67 was 14% or higher, 25,52 or higher than 20%.…”
Section: Ihc-based MC Er-positive Bcmentioning
confidence: 99%
“…Overall, the results of the present study may have important clinical implications. Considering the prognosis of luminal B/HER 2-negative cancer and the various profiles of hormonal and chemotherapy sensitivity, immunobiological stratification according to the expression of CD8 + TILs may improve the management of these patients (4,6). In addition, this type of immunological profiling may represent the first step towards a more improved understanding of the potential function of antitumor immune responses in mediating the clinical outcome of NC.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that luminal B BC exhibits a lower expression of hormone receptors, higher expression of proliferation markers and higher histologic grade compared with luminal A cancer (3,5). Furthermore, patients with luminal B cancer exhibit worse prognosis and have a distinct profile of response to hormonal and chemotherapy (4), and numerous efforts have been made to improve survival rates through early diagnosis and multiple therapies (6). However, the limitations of the current therapeutic modalities and advances in molecular diagnostics have resulted in increasing requirements for defining novel prognostic and predictive tools (7).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations